ANALISIS USABILITY PADA APLIKASI INDOFARM UNTUK MENGUKUR TINGKAT KEPUASAN PELANGGAN MENGGUNAKAN CUSTOMER SATISFACTION INDEX DAN USER EXPERIENCE QUESTIONNAIRE - Pramanda, Riska; Ilhamsyah; Mutiah, Nurul (P3M Politeknik Negeri Banjarmasin, 2024)
The rapid growth of digitalization has driven the expansion of E-Commerce, including the Indofarm application in Pontianak, which provides grocery delivery services. However, users have reported issues related to system performance and service quality. This study evaluates customer satisfaction using the Customer Satisfaction Index (CSI) and User Experience Questionnaire (UEQ) with 26 measurement indicators. The results show a CSI score of 52.70%, indicating a